The effects of task-oriented training on hand dexterity and strength in children with spastic hemiplegic cerebral palsy: a preliminary study - Moon, Jong-Hoon; Cho, Hwi-young; Hahm, Suk-Chan; Jung, Jin-Hwa (Journal of Physical Therapy Science, 2017)
[Purpose] The purpose of this study was to investigate the effects of task-oriented training (TOT) on hand dexterity and strength in children with spastic hemiplegic cerebral palsy. [Subjects and Methods] Twelve children with spastic hemiplegic cerebral palsy were randomly assigned to either the TOT group (n=6) or the control group (n=6). In both groups, conventional occupational therapy was performed 40-min/day, 2 times a week, for 4 weeks. In the TOT group, TOT was additionally performed for 20 min, and the control group received usual care. The box and block test (BBT) was performed to assess hand dexterity. Hand strength was also assessed using hand dynamometer. [Results] After intervention, the TOT group showed a significant improvement of hand dexterity. In the control group, BBT and grip strength were not significantly improved after intervention. [Conclusion] In clinical settings, we suggest that TOT may be used as an intervention to improve hand dexterity in children with spastic hemiplegic cerebral palsy.